2018
DOI: 10.1021/acssuschemeng.8b02046
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Nanomaterial Activity at the Organelle Level: Impacts on the Chloroplasts and Mitochondria

Abstract: One of the challenges potentially limiting the continued widespread commercial development and application of engineered nanomaterials (ENMs) is the still perceived lack of knowledge on their potential toxic effects. Although evidence has been accumulating on the biological effects of ENMs at the level of cells, tissues, and organisms, wide differences in design make the results so far obtained not easily comparable. More importantly, risk assessment procedures are not sufficiently harmonized. Experimental dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 155 publications
5
43
0
Order By: Relevance
“…Engineered nanomaterials have been shown previously to disrupt the energy balance within cells, likely due to mitochondrial-related impacts. 51,52 Impacts to mitochondrial function may account for the upregulation of metabolism related pathways observed here. Furthermore, LCO NPs have been shown previously to adsorb phosphate in solution.…”
Section: Subtoxic and Toxic Np Doses Upregulate Pathways That Fall Inmentioning
confidence: 82%
See 1 more Smart Citation
“…Engineered nanomaterials have been shown previously to disrupt the energy balance within cells, likely due to mitochondrial-related impacts. 51,52 Impacts to mitochondrial function may account for the upregulation of metabolism related pathways observed here. Furthermore, LCO NPs have been shown previously to adsorb phosphate in solution.…”
Section: Subtoxic and Toxic Np Doses Upregulate Pathways That Fall Inmentioning
confidence: 82%
“…7 illustrates hypothesized connections and possible explanations for the observed regulated processes, which represent potential areas for future studies. The upregulation of metabolism related processes by both subtoxic and toxic NP doses suggests energy imbalance or depletion, possibly due to mitochondrial disfunction, 51,52 and cellular attempt to restore balance. We hypothesize this energy imbalance could result from NP-induced hypoxia, as suggested by the observed upregulation of pathways related to decreased oxygen levels and hypoxia by both the toxic and subtoxic doses at 24 and 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Positive effects on chloroplast and mitochondria have been reported for various metal oxide nanoparticles. For instance, nano-TiO 2 protects the chloroplast and mitochondria from environmental stress via increasing antioxidant enzyme activities and up-regulating At3g23990 [34,35]. Similarly, the single-walled carbon nanotubes increase the photosynthetic activity and the threshold of electron transport due to their protective effects on lipid membranes in chloroplast [36].…”
Section: Discussionmentioning
confidence: 99%
“…From a physiological and molecular point of view, it has been demonstrated that ENMs increase the Reactive Oxygen Species (ROS) production within the cells. These excessive ROS interact negatively with all cell compartments, in particular affecting cell membranes and the energy production at the level of the mitochondria [43]. However, it remains unclear whether the generation of intracellular ROS could derive only from a direct interaction at the level of the mitochondria or if the ROS production at the level of the cytosol was also involved [43].…”
Section: Discussionmentioning
confidence: 99%
“…These excessive ROS interact negatively with all cell compartments, in particular affecting cell membranes and the energy production at the level of the mitochondria [43]. However, it remains unclear whether the generation of intracellular ROS could derive only from a direct interaction at the level of the mitochondria or if the ROS production at the level of the cytosol was also involved [43]. Measures of the cell redox state utilizing parameters related to the GSH oxidation state confirmed that in both tolerant and sensitive mutants, treated with CdS QDs, the oxidation level of glutathione was higher than in the not treated control (Figure 5, Tables S7 and S8).…”
Section: Discussionmentioning
confidence: 99%